STEGO: A Tool for Implementing Text-Audio-Video Steganography - Donga, Hitendra; Atkotiya, Kishor (International Journal of Computer Sciences and Engineering, 2025)
Steganography is the creative method of hiding any important information or data like passcode, data file, image; spreadsheets behind the original cover file. In this paper we proposed the text-audio-video cryptstego which is the combination audio steganography and video steganography using algorithm implemented using C#.Net tool and Libraries. The main goal of our research paper is to hide the important data file or any spreadsheet behind the audio, video, or image file and also one more method we have used is to store it as cipher text. Steganography can be used for hidden communication. We have explored the limits of steganography theory and practice. The implemented algorithm is 6LSB is used for image steganography. We made out the enhancement of the image steganography system using LSB approach to provide a means of secure communication. A proposed cryptstego-key has been applied to the system during embedment of the message into the cover image, it also provide the technique to hide plain text file or any other data behind bitmap image any audio file. So the proposed system secures the data transmission using proposed stego tool. This paper mainly focuses the idea of computer forensic technique and its use of audio-video steganography technique for providing better security in concern.